Biomecánica da movimentação ortodôntica--resposta inicial dos tecidos periodontais. - de Oliveira Ramalho, L. T.; Bozzo, L. (My University, 1990)
There occurs a biological response of the tissues of dental support, in answer to the external physiological forces and those realized during clinical treatments with orthodontical purposes. These forces differ from the first ones because they are continuous and time dependent. A great dental mobility is related to the degree of tissue organization of the periodontium system and the orthodontical movement must utilize this exceptional capacity of renewal and adaptation of the periodontium structures adequately. Therefore, through histological means a search was made to evaluate the succession of alterations of the periodontium system after the application of an orthodontical force on the molars of young rats and to interpret the standards of horizontal mobility and their consequences on the periodontium structures, biologically. An orthodontic force was applied on young rats utilizing steel wire placed in a ring form on a contact point between the first and second lower molars. The animals were sacrificed after 30 minutes, 1, 2, 6, 12, 24, 48, 72, 96 and 168 hours after the placement of the metal ring. After technical preparation, the microscopic slides were examined and the results were compared. In all the sections there was evidence of an intense metabolic activity. A gradual evolution of modification on the phenomenons had occurred.
Biomechanics of orthodontic movement--initial response of periodontal tissue
Keywords: animal; dental care; male; molar tooth; orthodontic device; periodontal disease; periodontium; physiology; rat; time; Animal; Dental Stress Analysis; English Abstract; Male; Molar; Orthodontic Appliances; Periodontium; Rats; Time Factors; Tooth Movement